2003
DOI: 10.1002/pen.10017
|View full text |Cite
|
Sign up to set email alerts
|

Nylon 10 10–montmorillonite nanocomposite made by intercalating polymerization

Abstract: Nylon 10 10–montmorillonite nanocomposite has been prepared successfully using intercalating polymerization. The nanocomposite was investigated by X‐ray diffraction (XRD), Fourier transform infrared (FTIR), Atom force microscopy (AFM), Scanning electron microscopy (SEM), Thermogravimetric analysis (TGA), Differential scanning calorimeter (DSC), and Dynamic mechanical analysis (DMA). The results show that there are uniformly dispersed silicate layers in the nylon 10 10 matrix. The resulting nanocomposites have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…The nylon 10,10–MMT nanocomposite was prepared by intercalating polymerization 9. The MMT was firstly modified with 11‐aminoundecanoic acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nylon 10,10–MMT nanocomposite was prepared by intercalating polymerization 9. The MMT was firstly modified with 11‐aminoundecanoic acid.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is possible to overcome these drawbacks through the preparation of a nylon 10,10–MMT nanocomposite. Recently, nylon 10,10–MMT nanocomposites have been prepared successfully by intercalating polymerization in our lab, and this nanocomposite has a higher modulus and onset temperature of decomposition compared with neat nylon 10,10 9…”
Section: Introductionmentioning
confidence: 99%
“…The intercalated nanocomposites, where the polymer chains are inserted between silicate layers but the well ordered multilayer morphology of the clay is still present, are usually achieved through solution blending and melt intercalation. [10][11][12][13][14][15] The exfoliated clay structure, where the silicate layers are completely delaminated into single sheets and randomly orientated in polymer matrix, could be possibly achieved through in situ polymerization. 3,[5][6][7][8] Weimer 5 reported a successful strategy to achieve exfoliated polystyrene/ layered silicate nanocomposites by in situ freeradical polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [123] have reported that the degree of crystallinity of Nylon 10,10/ clay nanocomposites remained almost constant, while the degree of supercooling decreased with the increase in clay content. This observation was attributed to the heterophase nucleation of Nylon 10,10 due to the presence of clay layers.…”
Section: Nylon 1010mentioning
confidence: 99%